2019
DOI: 10.1002/cite.201800202
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Electrolyte Imbibition in Gas Diffusion Electrodes

Abstract: The performance of the gas diffusion electrode (GDE) is most crucial for technical processes like chlor-alkali electrolysis. It is responsible to ensure intimate contact between gaseous reactants, catalyst, and electrolyte. The physically based contact line force model is employed to simulate the electrolyte imbibition into solid microstructures using the smoothed particle hydrodynamics method. Simulations are presented to show key aspects like the effect of heterogeneous solid substrates with different wettin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is known, that the electrodes are inhomogeneous in particle size, pore size distribution as well as in the local catalyst and binder loading [23] . These local inhomogeneities in turn lead to a distribution of hydrophilic and hydrophobic properties of the different pores [10] and may explain the previously observed electrolyte distribution [9] . The processes in the inhomogeneous threedimensional GDE are very complex and include the effects of microkinetics [34] , electrowetting [9] or closed pores [8] .…”
Section: Modellingmentioning
confidence: 69%
See 1 more Smart Citation
“…It is known, that the electrodes are inhomogeneous in particle size, pore size distribution as well as in the local catalyst and binder loading [23] . These local inhomogeneities in turn lead to a distribution of hydrophilic and hydrophobic properties of the different pores [10] and may explain the previously observed electrolyte distribution [9] . The processes in the inhomogeneous threedimensional GDE are very complex and include the effects of microkinetics [34] , electrowetting [9] or closed pores [8] .…”
Section: Modellingmentioning
confidence: 69%
“…They showed that the pore structure as well as the distribution of the electrolyte during operations is inhomogeneous: some pores were barely flooded by the electrolyte, whereas a local breakthrough of the electrolyte to the oxygen side was observed in other pores [9] . The locally high electrolyte saturation seems surprising, as previous studies have shown that even very small amounts of PTFE lead to a non-wettability of a pore system [10] . In conclusion, the influences of PTFE content and local inhomogeneities on ODC performance are not fully understood yet, no models to quantitatively describe this influence are available.…”
Section: Introductionmentioning
confidence: 91%